Subtractive library of soybean roots in response to inoculation with Bradyrhizobium japonicum. - CARVALHO, G. A. B. de (2012)
ABSTRACT: Soybean [Glycine max (L.) Merr.] is the most important legume cropped worldwide, with an economic value attributed mainly to the high protein content of the grain, which, in turn, demands a heavy supply of nitrogen. An environmentally friendly source of nitrogen at low cost to farmers is represented by the biological fixation of atmospheric nitrogen that takes place is association with symbiotic bacteria. For the soybean, the association occurs mainly with bacteria belonging to the species Bradyrhizobium japonicum and Bradyrhizobium elkanii, but our knowledge about gene expression associated with the symbiosis is still poor. This work - part of an effort by the Soybean Genome Consortium (Genosoja)?was conducted with the aim of achieving better understanding about the functionality of the genes expressed in soybean roots in the early stages of the interaction with B. japonicum. The study was performed with soybean plants growing under greenhouse conditions, inoculated (or not) with strain CPAC 15 (=SEMIA 5079) of B. japonicum, which is broadly used in Brazilian commercial inoculants. Total RNA was extracted, the mRNA was isolated and a subtractive library was constructed. Sequencing analysis generated 4,621,072 reads, which were assembled in 3,776 sequences, defined as the differentially expressed sequences of the inoculated versus non-inoculated treatments. The sequences were categorized according to their molecular function and grouped with representatives of antioxidant activities, molecular transduction, transporters and enzyme regulation activities, but with an emphasis on catalytic and molecular binding/signaling. RESUMO: A soja [Glycine max (L.) Merr.] é uma leguminosa de grande expressão mundial, com valor econômico atribuído, principalmente, ao teor proteico elevado dos grãos, que, por sua vez, demandam altas doses de nitrogênio. Uma fonte de nitrogênio ambientalmente favorável e de baixo custo para os agricultores é representada pela fixação biológica do nitrogênio atmosférico, que ocorre através da associação com bactérias simbióticas. Na soja, essa associação ocorre, principalmente, com bactérias das espécies Bradyrhizobium japonicum e Bradyrhizobium elkanii, mas o conhecimento sobre a expressão gênica associada com a simbiose ainda é escasso. Este trabalho ? parte integrante do Consórcio do Genoma da Soja (Genosoja) ? foi conduzido com o objetivo de obter um melhor entendimento sobre a funcionalidade dos genes expressos nas raízes de soja nos estágios iniciais da interação com B. japonicum. O estudo foi conduzido com plantas de soja cultivadas sob condições de casa de vegetação, inoculadas (ou não) com a estirpe CPAC 15 (=SEMIA 5079) de B. japonicum, utilizada em larga escala em inoculantes comerciais no Brasil. O RNA foi extraídos das raízes, o mRNA foi isolado e a biblioteca subtrativa construída. O Sequenciamento gerou 4.621.072 leituras que, após a montagem resultaram em 3.776 sequências, definidas como diferencialmente expressas dos tratamentos inoculado versus não inoculado. As sequências foram agrupadas de acordo com sua função molecular, que resultou nas categorias de atividade antioxidante, transdução molecular, transporte, regulação de atividades enzimáticas, mas com ênfase nas atividades catalíticas e de ligação/ sinalização molecular.